Hollow carbon sphere with open pore encapsulated MnO2 nanosheets as high-performance anode materials for lithium ion batteries. (10th January 2018) - Zang, Jun; Ye, Jianchuan; Qian, Hang; Lin, Yu; Zhang, Xiangwu; Zheng, Mingsen; Dong, Quanfeng
Abstract: A new structured hollow carbon spheres with an open pore (HCSO) were synthesized by introducing a pore-forming agent PEG. Unlike the conventional hollow particles, the void space is fully utilized due to the presence of the open pore. As a proof-of-concept, MnO2 nanosheets are in-situ grown on both the outer shell and the inner cavity of HCSO forming sandwich structure via a facile redox method, named MnO2 @HCSO composite. Meanwhile, the distance for lithium ion diffusion greatly reduces. When tested as an anode material for lithium ion batteries, MnO2 @HCSO composite exhibits increased performance compared to MnO2 /HCS composites which use traditional closed HCS as carbon matrix. It can still deliver a specific capacity of 398 mAh g −1 based on the whole mass of composite even when the current density was increased to 5 A g −1 . This special designed structure would be extended to different fields, such as sensors and catalyst.